TRAUMATIC GRIEF REACTION AS DEATH DETERMINANT AMONG THE AGED - USANG, ETENG ELOMA; EKPO, ENO BASSEY; UGWUMBA, NGOZI FRED (Advances in Social Sciences Research Journal, 2015)
ABSTRACT Thepurpose of this study was to find out common manifestations of traumatic grief, cultural variation of griefand what distinguishes normal behavior from traumatic grief among the aged. The research was carried out on the aged living at Good Samaritan Home in Calabar Metropolis of Cross River State, Nigeria. A survey questionnaire was administered on a sample size of twenty people from the Home in Calabar. A four point Likert-like rating scale was secured as the instrument for data collection and the questionnaire was first vetted and validated for data collection. The respondents indicated the extent of their agreement to the items based on the scale points; strongly agree, agree, disagree and strongly disagree The responses are weighted against the options and the mean score was derived by summing the weighted scores and dividing it by total number of responses. Keywords: traumatic, grief,old, age, death, year.